2020
DOI: 10.1101/2020.06.16.151308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cdc42 GTPase Activating Proteins (GAPs) Maintain Generational Inheritance of Cell Polarity and Cell Shape in Fission Yeast

Abstract: The highly conserved small GTPase Cdc42 regulates polarized cell growth and morphogenesis from yeast to humans. We previously reported that Cdc42 activation exhibits oscillatory dynamics in Schizosaccharomyces pombe cells. Mathematical modeling suggests that this dynamic behavior enables a variety of symmetric and asymmetric Cdc42 distributions to coexist in cell populations. For individual wild type cells, however, growth follows a stereotypical pattern where Cdc42 distribution is initially asymmetrical in yo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Meanwhile rga6∆ cells have been found to be slightly more monopolar, with smaller relative Cdc42 fluctuations compared to wild-type [39]. This comparison to experiments suggests that there is more to polarity regulation of these mutant cells than simply changing a single rate constant of our model (see recent results in [54]).…”
Section: Simulations With Reduced Gap II Recruitmentsupporting
confidence: 58%
“…Meanwhile rga6∆ cells have been found to be slightly more monopolar, with smaller relative Cdc42 fluctuations compared to wild-type [39]. This comparison to experiments suggests that there is more to polarity regulation of these mutant cells than simply changing a single rate constant of our model (see recent results in [54]).…”
Section: Simulations With Reduced Gap II Recruitmentsupporting
confidence: 58%
“…A recent report has shown that presence of the GAPs at the cortex prevents local Cdc42 activation even upon localization of the scaffold Scd2, which recruits Scd1 to the cortex (Lamas et al, 2020b). Another preprint suggests that Cdc42 GAP levels in daughter cells determine the pattern of polarized growth in those cells (Pino et al, 2020). These reports and our findings together indicate that loss of Rga4 from the cell ends after mitosis is necessary to allow Cdc42 activation at these ends, so long as the MOR pathway is active.…”
Section: Discussionmentioning
confidence: 99%
“…In higher eukaryotes, it is unknown whether Rho GAPs also regulate the cortical localization and function of septins. Another function of Rga6 in polarized growth might be to link the growth history of the mother cell to Cdc42 activation in daughter cells [160].…”
Section: Schizosaccharomyces Pombementioning
confidence: 99%